Coping with cyberbullying - Mc Guckin, Conor (Nova Science., 2017)
Each period of technological advancement brings with it excitement and opportunity whilst also being accompanied by worry and concern regarding the risk and potential harm posed to society - particularly its young. With the arrival of television there was concern that children would be exposed to unsuitable content, that they would damage their eyes by sitting too close to the television screen, and that their academic and intellectual development would be impaired and hindered. Similarly, widespread access to video games (especially violent ones) in the 1990s raised many of the same concerns. Historically, there were many other technological advances to create anxiety! Cassette players with earphones might have damaged the hearing of a generation. Before that, there was the supposed danger of records being played backwards to communicate satanic messages. In the 1800s, there was worry about the problem of students becoming overly reliant on paper and neglecting to learn how to properly use a slate and chalk, for when paper would inevitably be in short supply. In the first part of the 21st century, the focus has been firmly on Internet access, and in particular, the risks posed to children and young people (CYP). This brief look at historical advances and the challenges of technological progress begs the question - why do we always feel the need to “reinvent the wheel”? Just as those people who were alive at the beginning of the agricultural revolution or the industrial revolution faced challenges, those of us living through the “digital age” face new and previously unimaginable tests. Can we not, in a Piagetian manner, just assimilate the digital challenges into existing schemas - like the schema we all have for “coping” with other, more familiar stressors? However, in saying this, it must be acknowledged that the online world poses unique challenges.
Bullying and cyberbullying: Prevalence, psychological impacts and intervention strategies.
Keywords: Inclusive Society; ANTI-BULLYING POLICY; BULLY; BULLY-VICTIM; BULLY/VICTIM PROBLEMS; BULLYING; Bullying; Bullying; Bullying, Harassment and Violence in School & the Workplace; Cyberbullying; EDUCATION; School Bullying; Traditional Bullying; prevention of bullying; Children; Education; Social participation; Youth